Polyarenes Distribution in the Soil-Plant System of Reindeer Pastures in the Polar Urals - Elena Shamrikova; Evgeniia Yakovleva; Dmitry Gabov; Egor Zhangurov; Michail Korolev; Elya Zazovskaya (Agronomy, 2022)
Humic substances of soils consist of various organic compounds, including polycyclic aromatic hydrocarbons (PAHs). Soil as a fairly stable medium allows the correct use of polyarenes as markers of the humus formation process. Monitoring of the accumulation of PAHs as resistant organic toxicants is also necessary due to their carcinogenic and mutagenic properties. Natural plant resources serve as the feed base of northern reindeer husbandry. In this study, high-performance liquid chromatography in a gradient mode and gas chromatography-mass spectrometry methods were used to estimate the content of PAHs in mountain tundra and meadows of the Polar Urals (Russia). The accumulation of polyarenes in soils on carbonate rocks of the Bolshoi Paipudynsky ridge occurs mainly in the process of soil formation and largely depends on factors such as productivity of plant communities, the composition of standing biomass, the site’s position in relief, the granulometric composition of soils, cryogenesis process and pyrogenesis. According to the set of polyarenes, their number, and ratio, the studied objects were classified into separate groups by discriminant analysis. The most typical representatives of pedogenic origin are naphthalene and phenanthrene. The accumulation features of dibenz[a,h]anthracene and benz[b]-, benz[k]fluoranthene, benz[ghi]perylene, and benz[a]perylene are shown. In mountain tundra landscapes, the characteristics of PAHs can be used to diagnose the intensity and direction of soil formation processes in general and humification in particular.